IMPLEMENTASI PENDIDIKAN INKLUSI PADA SISWA SLOW LEARNER DI MI AN-NAZWA CIKEUSAL KABUPATEN SERANG - Dirga Ayu Lestari (LPPM Universitas Bina Bangsa, 2023)
The purpose of this research is to dig deeper into inclusive education in schools to provide special support to creative teachers to create creative, interesting, fun and complete learning activities. This study uses a qualitative method with a descriptive approach. According to Sugiyono, qualitative methods are usually called naturalistic research methods. The data collection techniques in this study are observation, interviews and documentation. The data analysis techniques are data reduction, data presentation and drawing conclusions. The discussion in this study explains the planning of implementing thematic learning for slow learner students at MI An-Nazwa Cikesal, namely by looking at intelligence, children usually have an IQ below the age of normal children, learning abilities are slower. And social children tend to be more silent. While the implementation of thematic learning for slow learner students in the preliminary stages of learning activities is carried out with direct practice and various methods according to the themes being studied. Furthermore, in the core activities each teacher has a different way of interacting. Furthermore, in the closing activity, reviewing the learning material that has been applied or working on the questions given by the teacher, giving a motivational boost so that students have a sense of enthusiasm in carrying out learning activities